LncRNA Nron Inhibits Bone Resorption in Periodontitis. (February 2022) - Li, J.; Jin, F.; Cai, M.; Lin, T.; Wang, X.; Sun, Y.
Periodontitis is the most common chronic oral disease and is characterized by active osteoclast activity and significant alveolar bone resorption. However, the key regulatory factors of periodontal bone loss have yet to be determined, and reasonable intervention methods for periodontitis have not been developed. Currently, long noncoding RNAs (lncRNAs) have shown a remarkable ability to maintain normal cell and tissue homeostasis. Interestingly, we recently found that the lncRNA Nron is negatively correlated with alveolar bone resorption in periodontitis model. To explore the role of Nron in periodontal bone loss, osteoclastic-specific Nron knockout mice and osteoclastic-specific Nron transgenic mice were generated. Nron effectively inhibited osteoclastogenesis and alveolar bone resorption. Mechanistically, Nron was found to effectively promote the nuclear transport of NF-κb repressing factor (NKRF). In addition, NKRF in the nucleus significantly repressed the transcription of Nfatc1, which is a major NF-κb signaling molecule. Importantly, local injection of the Nron overexpression vector significantly inhibited osteoclastogenesis and alveolar bone resorption, which indicated the translational application potential of lncRNAs in the treatment of bone resorption in periodontitis.